Pengaruh Digitalisasi Pembayaran SPP Terhadap Kepuasan Wali Murid di Sekolah Dasar Islam Terpadu Al-Ishlah Sampit - Rusmaniah, Rusmaniah; Hilaliyah, Sari Atul (Keizai, 2025)
The emergence of digitalization in the education sector has prompted numerous schools to adopt technological innovations, including in the payment of tuition fees. This digital transformation is anticipated to enhance efficiency, transparency, and convenience for parents or guardians. However, the implementation of digital payment systems at SDIT Al-Ishlah Sampit has encountered several challenges, such as technical difficulties and varying levels of user adaptability, thereby raising questions regarding its impact on parental satisfaction. Furthermore, existing literature examining the specific influence of digitalization on parental satisfaction remains limited, indicating a need for further investigation to address this research gap. This study aims to analyze the effect of digital tuition payment systems on parental satisfaction. A quantitative approach was employed, involving a survey of 100 respondents drawn from a total population of 193 parents or guardians. Primary data were collected using a Likert-scale questionnaire distributed both online via WhatsApp groups and in-person during the school’s monthly meetings. The findings reveal that digital tuition payment systems have a positive effect on parental satisfaction. Key factors such as ease of access, transaction speed, and transparency significantly contribute to increased satisfaction. Additionally, responsiveness, assurance, and perceived educational costs were found to have a positive influence, while physical evidence and reliability showed no significant impact on parental satisfaction.